Glucose Intolerance after a Recent History of Gestational Diabetes - Benhalima, Katrien (Hindawi Publishing Corporation, 2014)
Aim. Our aim was to evaluate the uptake of our current screening strategy postpartum and the risk factors for glucose intolerance in women with a recent history of gestational diabetes (GDM). Methods. Retrospective analysis of files of women with a recent history of GDM diagnosed with the Carpenter and Coustan criteria from 01-01-2010 till 31-12-2013. Multivariable logistic regression was used to adjust for confounders. Results. Of all 231 women with a recent history of GDM, 21.4% (46) did not attend the scheduled postpartum OGTT. Of the women tested, 39.1% (66) had glucose intolerance and 5.3% (9) had diabetes. These women were more often overweight (39.7% versus 25.3%, P = 0.009), were more often treated with basal-bolus insulin injections (52.0% versus 17.4%, P = 0.032), and had a lower beta-cell function and lower insulin sensitivity, remaining significant after adjustment for age, BMI, and ethnicity (insulin secretion sensitivity index-2 (ISSI-2) in pregnancy 1.5 ± 0.5 versus 1.7 ± 0.4, P = 0.029; ISSI-2 postpartum 1.5 (1.2–1.9) versus 2.2 (1.8–2.6), P = 0.020; Matsuda index postpartum 3.8 (2.6–6.2) versus 6.0 (4.3–8.8), P = 0.021). Conclusion. Glucose intolerance is frequent in early postpartum and these women have a lower beta-cell function and lower insulin sensitivity. One fifth of women did not attend the scheduled OGTT postpartum.